The Amborella vacuolar processing enzyme family - Poncet, Valérie; Scutt, Charlie; Tournebize, Rémi; Villegente, Matthieu; Cueff, Gwendal; Rajjou, Loic; Balliau, Thierry; Zivy, Michel; Fogliani, Bruno; Job, Claudette; De Kochko, Alexandre; Burtet-Sarramegna, Valerie; et al. (Frontiers in Plant Science, 2015)
Most vacuolar proteins are synthesized on rough endoplasmic reticulum as proprotein precursors and then transported to the vacuoles, where they are converted into their respective mature forms by vacuolar processing enzymes (VPEs). In the case of the seed storage proteins, this process is of major importance, as it conditions the establishment of vigorous seedlings. Toward the goal of identifying proteome signatures that could be associated with the origin and early diversification of angiosperms, we previously characterized the 11S-legumin-type seed storage proteins from Amborella trichopoda, a rainforest shrub endemic to New Caledonia that is also the probable sister to all other angiosperms (Amborella Genome Project, 2013). In the present study, proteomic and genomic approaches were used to characterize the VPE family in this species. Three genes were found to encode VPEs in the Amborella's genome. Phylogenetic analyses showed that the Amborella sequences grouped within two major clades of angiosperm VPEs, indicating that the duplication that generated the ancestors of these clades occurred before the most recent common ancestor of living angiosperms. A further important duplication within the VPE family appears to have occurred in common ancestor of the core eudicots, while many more recent duplications have also occurred in specific taxa, including both Arabidopsis thaliana and Amborella. An analysis of natural genetic variation for each of the three Amborella VPE genes revealed the absence of selective forces acting on intronic and exonic single-nucleotide polymorphisms among several natural Amborella populations in New Caledonia.